233. The Epidemiology, Genomics, and Evolution of Staphylococcus aureus in Northeast Ohio - Watkins, Richard R (Open Forum Infect Dis, 2019)
BACKGROUND: Infections due to S. aureus result in significant morbidity, mortality, and healthcare expense. We sought to identify the strains of S. aureus causing infections in hospitalized patients in Northeast Ohio and determine whether they are reflective of the S. aureus strains present in the surrounding environment. METHODS: The study was approved by the Institutional Review Board at Cleveland Clinic Akron General. Clinical S. aureus isolates (n = 300) were cultured and PCR was used to amplify the staphylococcus protein A (spa), Panton–Valentine Leukocidin (PVL), and mecA genes. The clinical spa types were compared with ones from our data base of S. aureus strains previously collected and sequenced from the community and environment in Northeast Ohio. RESULTS: A total of 51 spa types were detected from 129 S. aureus clinical isolates (discriminatory index, 0.876; 95% confidence interval [CI], 0.827–0.925; Table 1). The most common spa types were t008 (42/129, 32.6%), t002 (16/129, 12.4%), and t334 (6/129, 4.7%). In comparison, the most frequently detected spa types from the environmental samples were t189 (40/257, 15.6%), t002 (16/257, 6.2%), and t008 (11/257, 4.3%). Among the S. aureus isolates (n = 146), 45 were PVL-positive (30.8%) and 94 (66.7%) carried mecA. Of the 42 t008 (ST8/USA300; a common community-associated strain) isolates, 35 (83.3%) were methicillin-resistant S. aureus (MRSA) (based on the presence of the mecA gene) and 25 (59.5%) were PVL-positive. Thirteen of the sixteen (81.2%) t002 (ST5/USA100; a common hospital-associated strain) were MRSA and only one (6.2%) was PVL-positive. CONCLUSION: There is considerable overlap of S. aureus strains present in clinical samples with those found in the environment. This finding should draw attention to the need for more effective prevention strategies to reduce the risk of transmission of S. aureus, including MRSA, in the environment to humans. [Image: see text] [Image: see text] DISCLOSURES: All authors: No reported disclosures.